Massive vector fields in Kerr-Newman and Kerr-Sen black hole spacetimes - Cayuso, Ramiro; Dias, Oscar J.C.; Gray, Finnian; Kubizňák, David; Margalit, Aoibheann; Santos, Jorge E.; Souza, Renato Gomes [UNESP]; Thiele, Leander (Springer Nature, 2020)
The superradiant instability modes of ultralight massive vector bosons are studied for weakly charged rotating black holes in Einstein-Maxwell gravity (the Kerr- Newman solution) and low-energy heterotic string theory (the Kerr-Sen black hole). We show that in both these cases, the corresponding massive vector (Proca) equations can be fully separated, exploiting the hidden symmetry present in these spacetimes. The resultant ordinary differential equations are solved numerically to find the most unstable modes of the Proca field in the two backgrounds and compared to the vacuum (Kerr black hole) case.
Keywords: Black Holes; Black Holes in String Theory